2010
DOI: 10.1177/1933719109358456
|View full text |Cite
|
Sign up to set email alerts
|

Tocolytic Effect of Δ9-Tetrahydrocannabinol in Mice Model of Lipopolysaccharide—Induced Preterm Delivery: Role of Nitric Oxide

Abstract: Delta(9)-Tetrahydrocannabinol contributes to the regulation of gestational duration in LPS-induced preterm delivery probably by NO coupling through the CB1 receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The doses and the treatments were based on the following past literature: for JZL184 [7][8], for AM281 [16] and for AM630 [17][18]. …”
Section: Methodsmentioning
confidence: 99%
“…The doses and the treatments were based on the following past literature: for JZL184 [7][8], for AM281 [16] and for AM630 [17][18]. …”
Section: Methodsmentioning
confidence: 99%
“…In earlier studies, the stimulation of the CB receptor led to the relaxation of the skeletal muscles 37,38 , smooth muscles of blood vessels 39 , and uterine smooth muscles 40 . Therefore, the stimulation of the CB receptors in the uterus was described as tocolysis 41 . As a result, a decrease in level of the receptors could lead to preterm uterine contractions and PTB.…”
Section: Discussionmentioning
confidence: 99%
“…However, if phytocannabinoids alter this dynamic process remains unclear and needs to be further investigated. It has been shown that chronic administration of ∆9-THC before LPS exposure at GD 15 significantly reduced LPS-induced preterm births and increased gestational duration, an effect reversed by the CB1 antagonist AM281, and NOS inhibitor administration [ 211 ]. ∆9-THC and CBD were also found to be effective in alleviating the LPS-induced cytokine storm in human macrophages trough the modulation of NPRL3 inflammasome and STAT3 signaling [ 212 ].…”
Section: The Role Of Endocannabinoids In Low-grade Inflammation and M...mentioning
confidence: 99%